Internet racism, journalism and the principle of public access: ethical challenges for qualitative research into 'media attractive' court cases. Issue 11 (1st September 2016) - Elsrud, Torun; Lalander, Philip; Staaf, Annika
ABSTRACT: This paper addresses the risk of research exposing people with an immigrant background in criminal court cases to Internet-based racist persecution, due to mismanagement of general ethical guidelines. The principle of informed consent, ideally serving to protect people under study from harm may, in fact, cause them more harm due to the interest among certain Internet-based networks of spreading identifiable, degrading information. Arguments are based on ethically challenging experiences from two ethnographic research projects carried out in Swedish district court environments, focused on immigrant court cases. Ethical advice provided by ethical review boards and established research guidelines, were based on an unawareness of the potentially destructive rendezvous in media attractive immigrant court cases between 'ethically informed' research, crime journalism, freedom of information legislation and 'Internet vigilantes' on a quest to persecute court participants and their families in the global digital arena.